2013
DOI: 10.1063/1.4799641
|View full text |Cite
|
Sign up to set email alerts
|

Structural reconstruction and defects transition in mediating room temperature ferromagnetism in Co-doped ZnO film

Abstract: Room temperature (RT) ferromagnetism (FM) was achieved in H2/N2 annealed Co-doped ZnO films on silicon substrates and we got annealing temperature, Tan, dependence of saturation magnetization, Ms, which increased and finally reached a maximum as Tan elevated. The curve of Ms versus Tan seems like three steps. Surprisingly, after sequential oxygen annealing, Ms of each annealed film decreased abruptly at first, and then restored to its original order after the second annealing, which may owe to the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Such devices typically make use of both spin and charge. The ferromagnetism observed in these compounds has been attributed to a variety of mechanisms including effects arising from transition metal ions, point defects, changes in the carrier concentration and grain boundaries [4][5][6][7][8][9][10][11]. Interestingly, ferromagnetism is also seen in some non-magnetic compound systems, such as pure HfO 2 films (about 5 Am 2 /kg) [12] and other nano-structures such as of ZnO films (about 1.0 emu/cm 3 ) [13] and pure TiO 2 powder (0.06 emu/g) [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices typically make use of both spin and charge. The ferromagnetism observed in these compounds has been attributed to a variety of mechanisms including effects arising from transition metal ions, point defects, changes in the carrier concentration and grain boundaries [4][5][6][7][8][9][10][11]. Interestingly, ferromagnetism is also seen in some non-magnetic compound systems, such as pure HfO 2 films (about 5 Am 2 /kg) [12] and other nano-structures such as of ZnO films (about 1.0 emu/cm 3 ) [13] and pure TiO 2 powder (0.06 emu/g) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, many groups have focused on doped, transition or rare earth, compound semiconductors such as Co:TiO 2 [4], Co:ZnO [5], Li:SnO 2 [6], and Cr:In 2 O 3 [7] due to their prospective applications in spintronic devices. Such devices typically make use of both spin and charge.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have demonstrated that the defects or oxygen vacancies (V o ) have significant influence on the room-temperature FM in TM doped ZnO films [26][27][28][29]. The FM is stronger in Zn 0.98 Cr 0.02 O film when the substrate temperature is 300°C, which is related to the increase of the number of defects and oxygen vacancies producted by the poor crystallization quality [30].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the use of ZnO in new magneto-optical applications is difficult because of their diamagnetic and paramagnetic behaviors at room temperature. Room temperature ferromagnetism (RTFM) in ZnO has been reported to result from vacancy mediation [15][16][17]. Several works have been carried out to improve the RTFM in ZnO by substituting the Zn atom with dopants of transition metals and rare earths.…”
Section: Introductionmentioning
confidence: 99%